Developing “Snakes and Ladders Speaking” Game-Based Learning Media to Enhance Arabic Speaking Skills at Madrasah Ibtidaiyah: Pengembangan Media Pembelajaran Berbasis Game “Ular Tangga Berbicara” untuk Meningkatkan Keterampilan Berbicara Bahasa Arab di Madrasah Ibtidaiyah - Rahma, Wieke; Kholisin; Dariyadi, Mochammad Wahib (UIN Raden Mas Said Surakarta, 2025)
Arabic language learning in elementary schools often emphasizes vocabulary memorization, creating a gap between linguistic knowledge and communicative competence. This study aims to develop a learning medium called Ular Tangga Berbicara, a game-based instructional tool combined with engaging illustration to train students maḥārah al-kalām (speaking skills). This study employs Design-Based Research within a game-based learning framework, utilizing the ADDIE model to develop and test the media's effectiveness. The results show that the develop media was validated by material and media experts, obtaing feasibility scores of 98% and 92.7% , respectively. The field trials received positive responses from students with a score of 84.36% and from teacher with 95.65%. Therefor, the Ular Tangga Berbicara media is considered valid and feasible to be used as a learning tool for improving Arabic speaking skilss among Grade V students at MI ummul Akhyar. The study demonstrates how game-based pedagogy can bridge traditional vocabulary acquisition with contemporary communicative language teaching approaches in Arabic education.